Cover Picture: Selective Synthesis of Partially Protected Nonsymmetric Biphenols by Reagent‐ and Metal‐Free Anodic Cross‐Coupling Reaction (Angew. Chem. Int. Ed. 39/2016). Issue 39 (28th July 2016) - Wiebe, Anton; Schollmeyer, Dieter; Dyballa, Katrin M.; Franke, Robert; Waldvogel, Siegfried R.
Abstract : Rotation about the biaryl axis leads to higher yield and selectivity in the electrochemical cross‐coupling giving partially protected 2, 2′‐biphenols. In their Communication onpage 11801 ff. S. Waldvogel and co‐workers report the first direct synthesis of partially protected nonsymmetric biphenols by oxidative cross‐coupling. The combination of the bulky triisopropylsilyl (TIPS) group and the solvent 1, 1, 1, 3, 3, 3‐hexafluoropropan‐2‐ol greatly broadens the scope of this sustainable synthesis.